A Hybridized Lobatto Quadrature of Precision Eleven for Numerical Integration of Analytic Functions - Sanjit Kumar Mohanty, Rajani Ballav Dash (Mathematical Statistician and Engineering Applications, 2023)
A hybridizedeleven precision quadrature rule using Lobatto 6-point rule and modified form of Lobatto 4-point rule through kronrod extension is formed. This rule is capable of evaluating line integral of analytic functions. The hybridized rule has been tested both theoretically through error analysis and numerically using some test integrals. It is found that the constructed rule is more effective than that of theconstituent rules. It is alsoverified that the hybridized rulewhen appliedin adaptive environment gives significantly better results than its constituents.